Correlation Study on HLA-DR and CD117 (c-Kit) Expressions: Its Prognosis and Treatment Response in Acute Myeloid Leukemia Patients - El-Meligui YM; Abd Elrhman HE; Salahuddin A; Hamouda MA; Kassem AB (Dove Medical Press, 2021)
Yomna M El-Meligui,1 Heba E Abd Elrhman,2 Ahmad Salahuddin,3 Manal Ali Hamouda,4 Amira B Kassem5 1Department of Clinical Pathology, National Cancer Institute, Cairo University, Cairo, Egypt; 2Department of Clinical Pathology, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 3Biochemistry Department, Faculty of Pharmacy, Damanhour University, Damanhour, Egypt; 4Clinical Pharmacy Department, Faculty of Pharmacy, Ahram Canadian University, Giza, Egypt; 5Clinical Pharmacy and Pharmacy Practice Department, Faculty of Pharmacy, Damanhour University, Damanhour, EgyptCorrespondence: Amira B Kassem Email amira.kassem@pharm.dmu.edu.egIntroduction: Acute myeloid leukemia (AML) is the most common type of acute leukemia in adults. HLA-DR and CD117 (c-Kit) are important diagnostic markers of AML. Our objective is to determine the prognostic significance of HLA-DR and CD117 expressions in newly diagnosed AML patients and determine the correlation between HLA-DR and CD117 expressions and other prognostic markers such as cytogenetic abnormalities, FLT3-ITD, response to treatment, and patient’s survival.Methods: This study included 100 newly diagnosed AML patients. All patients were subjected to clinical, morphological, cytochemical, cytogenetic analysis, molecular genetic analysis to detect FLT3-ITD, and Flowcytometric detection of HLA-DR, CD117, and CD 34.Results: The results showed that HLA-DR expression was found in 75 patients (77.3%), while CD117 expression was found in 63 patients (64.9%). Patients with HLA-DR expression showed significantly higher mean Hb concentration, significantly higher platelet count, associated with AML-FAB subtypes (M0, M1, and M2), CD34 expression, and favorable cytogenetic group. M3 subtype was significantly associated with HLA-DR-ve. While patients with CD117 expression showed significantly lower platelets count. Double positive patients (HLA-DR+ve/CD117+ve) showed significant association with the intermediate cytogenetic group, while double-negative patients (HLA-DR-ve/CD117-ve) were associated with the favorable and intermediate cytogenetic group and either positive (HLA-DR+ve /CD117-ve or HLA-DR-ve/CD117+ve) associated with poor cytogenetic groups. FLT3-ITD expression had significantly worse overall survival.Conclusion: The current study suggested that the expression of CD117 and HLA-DR may be a prognostic marker in AML, as they are associated with M0, M1, and M2 FAB subtypes; moreover, patients with combined HLA-DR and CD117 positive expression are associated with CD34 expression and intermediate cytogenetic group.Keywords: acute myeloid leukemia, HLA-DR, CD117, CD34, FLT3-ITD, response, cytogenetic